2014
DOI: 10.1007/s12663-014-0720-y
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and Postoperative CT Scan Assessment of Pterygomaxillary Junction in Patients Undergoing Le Fort I Osteotomy: Comparison of Pterygomaxillary Dysjunction Technique and Trimble Technique—A Pilot Study

Abstract: Purpose To determine the rate of complications and occurrence of pterygoid plate fractures comparing two techniques of Le Fort I osteotomy i.e., Classic Pterygomaxillary Dysjunction technique and Trimble technique and to know whether the dimensions of pterygomaxillary junction [determined preoperatively by computed tomography (CT) scan] have any influence on pterygomaxillary separation achieved during surgery. Materials and methods The study group consisted of eight South Indian patients with maxillary excess.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
(42 reference statements)
1
17
0
Order By: Relevance
“…Consistent with our results, several other researchers have found a negative correlation between the thickness of the pterygoid junction and the occurrence of the pterygoid plate fracture 5 , 21 , 22 . They hypothesized that when the pterygomaxillary junction is thin, the force from the osteotome may be easily dissipated leading to unwanted pterygoid plate fracture.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our results, several other researchers have found a negative correlation between the thickness of the pterygoid junction and the occurrence of the pterygoid plate fracture 5 , 21 , 22 . They hypothesized that when the pterygomaxillary junction is thin, the force from the osteotome may be easily dissipated leading to unwanted pterygoid plate fracture.…”
Section: Discussionsupporting
confidence: 93%
“…In an attempt to avoid these complications, some authors perform the osteotomy through the maxillary tuberosity, as described by Trimble 35 . They asserted that it reduced unfavorable fractures of the pterygoid plates 36 compared to traditional disjunction, and also increases the safety margin to the structures of the sphenopalatine fossa, reducing the incidence of hemorrhages 21 , 35 . One drawback is that the method can only be performed if the wisdom teeth are removed.…”
Section: Discussionmentioning
confidence: 99%
“…The width of the pterygomaxillary joint has been previously studied in articles related to surgical techniques such as Le Fort I osteotomies 27,28 . However, we have not been able to find research focused on implantology that evaluates this characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…As for the angulation of the pterygoid implants with respect to the Frankfort plane, there is no consensus. Different authors defend their placement with an approximate angle of 45° 13,15,35 while in more recent studies their placement is defended at an angle of 70° 2735 . In a study developed by Rodríguez et al .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Dadwal et al suggested that the 'Trimble technique' be applied, in which a vertical cut is made on the tuberosity in the third molar region, avoiding unfavourable pterygoid process fracture during LFI. 36 The present authors believe that, when cutting the pterygomaxillary junction, all the stress produced by the separation force is concentrated on the pterygoid process, leading to pterygoid process fracture. Therefore, in order to prevent pterygoid process fracture, the cut in the lateral wall of the maxilla should be limited to the middle point between the distal plane of the second molar and the pterygomaxillary junction.…”
Section: Pterygomaxillary Junctionmentioning
confidence: 75%